Konsep Perencanaan Tata Ruang Untuk Pengembangan Ekonomi Masyarakat Pulau Barrang Caddi Kota Makassar - Rahmiyatal Munaja; Shirly Wunas; Suriana La Tanrang (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2015)
Small islands have enormous economic potential related to the fisheries and marine sector. The increasing population and the continued development of community economic activities have an impact on the stability of land and the environment within the island's space. This study aims to identify the physical and environmental carrying capacity of the community's economy and develop spatial planning concepts for the economic development of the Barangdi Caddi Island community, Makassar City. The analytical method used is the analysis of land tensile capacity based on water availability or land cover and map overlay to determine the amount of space used for economic activities. The results of this study indicate that, physical and environmental aspects have an important role for the sustainability and development of economic activities. However, these aspects do not yet have the maximum carrying capacity of economic activities and their development on Barrang Caddi Island. The physical carrying capacity that supports economic activities is the location of fish cages with good depth, while the environmental carrying capacity is a gentle topographical condition for duck maintenance. The planning concept that will be applied is the division of the island into 3 zones, namely, the zone of preservation, intensive use, and conservation. The placement of this zone pays attention to important aspects related to island spatial planning namely, physical and environmental carrying capacity and aspects of community economic activities.